Analisis Emisi Karbon di Kesatuan Hidrologi Gambut Sungai Mendahara - Sungai Batanghari - Firdaus, M. Ismi; Syarifuddin, Hutwan; Zuhdi, Mohd (Universitas Batanghari Jambi, 2024)
Global Warming Due to Carbon Emissions is a threat to life on earth. According to the World Meteorological Organization, the earth's temperature rose by 1.06 °C to 1.26 °C above pre-industrial levels (1850–1900). According to the IPCC report (2021), the impacts of climate change will reach all regions in the world without exception. Indonesia's commitment to reduce carbon emissions by 29% with its efforts and 41% with international cooperation until 2030. Analysis of land cover uses the Unsupervised Classification, the method for calculating carbon emissions above the surface uses the IPCC method, namely the stock differential and the method for analyzing emissions of peat decomposition uses the Hooijer formula et al. (2006, 2010) with estimated water level from the TMAT BRGM data regression equation with NDWI Landsat 8 values then total carbon emissions by adding emissions from above and below the surface. Based on the results of the analysis of land cover at the research location, the area was dominated by plantations at 37.8%, while the forest area was only 7.9%. Ground carbon emissions average 0.23 Mt CO2-eq per year, below Ground carbon emissions are 9.94 Mt CO2-eq and total carbon emissions are 10.17 Mt CO2-eq with total emissions from 2013 - 2022 of 91.6 Mt CO2-eq Carbon emissions in KHG Sungai Mendahara - Batanghari graphically fluctuate, there is an increase and decrease but tends to increase until 2022 this is due to land conversion and massive land clearing in forest areas and the biggest contributor to carbon emissions from decomposition peatlands.